An Analysis on Listening Comprehension Difficulties Among Grade VII-E Students at SMP Negeri 4 Kediri - Ni Kadek Keristina Wati; Putu Santi Oktarina; Ni Wayan Satri Adnyani (Indo Publishing, 2026)
The purpose of this study was to find out what aspects of listening difficulties are experienced by students, the types of listening difficulties experienced by students and the factors that influence them. This study used a descriptive qualitative method of case study type. This study used VII-E class of SMP Negeri 4 Kediri as a sample with a total of 29 students. The test results showed that students experienced difficulties in the listening for specific information (implicit) with percentage 71.6% while the lowest percentage was listening for inference with percentage 48.9%. The students felt the classroom was noisy, they could not hear the audio clearly, foreign words, lost concentration, lack of vocabulary and did not understand the audio. Based on the close-ended questionnaire the result showed that dominant difficulties faced by students in contextual difficulties especially noisy classroom and speaker difficulties especially speaking speed. Furthermore, students also faced stimulus difficulties especially in grammar and listener especially vocabulary. This is due to their limited vocabulary, loss of concentration, audio is too fast, the noisy classroom and long text. Based on the results of semi-structured interviews, students experienced difficulties caused by both internal and external factors. Internal factors such as lack of concentration and limited vocabulary. Meanwhile, external factors, such as noisy classrooms, audio that is too fast and unclear, and unfamiliar accents. From these results, it can be concluded that students experience the highest difficulty in the aspect of listening for specific information, they also experience dominant contextual difficulties, especially difficulties in noisy classroom, speaker difficulties especially in speaking speed, stimulus difficulties, especially in grammar and listener difficulties especially in vocabulary. It means that they experienced difficulties caused by internal and external factors.